Disturbed Pitch Perception during Antidepressant Therapy of a Combination of Lithium, Nortriptyline, and Oxazepam: A Rare Unexpected and Undesirable Side Effect for a Violinist - Siwert de Groot (Case Reports in Otolaryngology)
Disturbed pitch perception is a rare but well-known side effect of the antiepileptic drug carbamazepine and its derivates. A patient is presented who used three antidepressants because of depression. After recovering, the medication was continued, but as a violinist, the patient was told that his intonation was too low with the consequence that he was not allowed to participate in the orchestra where he had been for years. After phasing out the medications, his pitch perception returned to normal. This observation is unique as no other examples of this side effect are found in the literature in relation to antidepressants.